The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.gofs.2017.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Exposition aux risques professionnels pendant la grossesse : retour de services médicaux interentreprises

Abstract: Our results argue for the need to follow pregnancies at work. However, the low level of prevention activities and the high level of sick leaves raise the question of the management of pregnant women at work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…The characteristics of our study population were close to those of the French population of postpartum women in 2016 [34]. Overall, our results are largely consistent with the findings of other French studies, as already discussed [16,17,18].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The characteristics of our study population were close to those of the French population of postpartum women in 2016 [34]. Overall, our results are largely consistent with the findings of other French studies, as already discussed [16,17,18].…”
Section: Discussionsupporting
confidence: 92%
“…In the workplace, one study carried out in France showed that, although exposure to occupational risk is frequent among pregnant workers, prevention is still very limited [18]. This study did not investigate the women’s perceptions concerning occupational risks or personal behavioral changes.…”
Section: Introductionmentioning
confidence: 99%
“…Limiting exposure to environmental factors should not only be conducted at the individual level. Other actions must also be implemented through (1) regulation, which makes it possible to avoid widening social inequalities in health by not stigmatizing people who are not in a behavioral change process; (2) communication on the appropriate actions to adopt, issued directly to the general population (for example, advice to young adults of childbearing age on the abandonment of unfavorable practices, such as the use of indoor pesticides, candles, and air fresheners); and (3) a specific approach to risk prevention at work, in particular by modifying or adapting the jobs of women who wish to conceive [20]. Indeed, more than 50% of the patients received at the ARTEMIS Center were shown to have been exposed to reproductive risk factors in the workplace.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, more than 50% of the patients received at the ARTEMIS Center were shown to have been exposed to reproductive risk factors in the workplace. In France, there are regulatory provisions to protect pregnant women, but reproductive risk is poorly known and, therefore, poorly identified, both by occupational health services and employers and their employees [20]. As a result, the preventive and protective measures associated with such risk are often inadequate or nonexistent (especially for men).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified organizations' shortcomings in the implementation of maternity protection measures, including the absence of a risk assessment and the absence, or inadequacy, of workplace accommodation (Adams et al, 2016a(Adams et al, , 2016bLembrechts & Valgaeren, 2010;Rudin et al, 2018). These shortcomings were also observed in the healthcare sector (Abderhalden-Zellweger et al, 2021;Henrotin et al, 2018). As a result, some employees face a dilemma: ask for sick leave to withdraw from a perceived dangerous work environment, with its potentially negative consequences on their career, professional relationships and salary, or work in an environment that is potentially dangerous to their health and that of their unborn child (Malenfant, 2009).…”
Section: Introductionmentioning
confidence: 99%